Targeted gene panel sequencing for the rapid diagnosis of acutely ill infants. Issue 7 (13th June 2019) - Brunelli, Luca; Jenkins, Sabrina M.; Gudgeon, James M.; Bleyl, Steven B.; Miller, Christine E.; Tvrdik, Tatiana; Dames, Shale A.; Ostrander, Betsy; Daboub, Josue A. F.; Zielinski, Brandon A.; Zinkhan, Erin K.; Underhill, Hunter R.; et al.
Abstract: Background: Exome/genome sequencing (ES/GS) have been recently used in neonatal and pediatric/cardiac intensive care units (NICU and PICU/CICU) to diagnose and care for acutely ill infants, but the effectiveness of targeted gene panels for these purposes remains unknown. Methods: RapSeq, a newly developed panel targeting 4, 503 disease‐causing genes, was employed on selected patients in our NICU/PICU/CICU. Twenty trios were sequenced from October 2015 to March 2017. We assessed diagnostic yield, turnaround times, and clinical consequences. Results: A diagnosis was made in 10/20 neonates (50%); eight had de novo variants ( ASXL1, CHD, FBN1, KMT2D, FANCB, FLNA, PAX3 ), one was a compound heterozygote for CHAT, and one had a maternally inherited GNAS variant. Preliminary reports were generated by 9.6 days (mean); final reports after Sanger sequencing at 16.3 days (mean). In all positive infants, the diagnosis changed management. In a case with congenital myasthenia, diagnosis and treatment occurred at 17 days versus 7 months in a historical control. Conclusions: This study shows that a gene panel that includes the majority of known disease‐causing genes can rapidly identify a diagnosis in a large number of tested infants. Due to simpler deployment and interpretation and lower costs, this approach might represent an alternative to ES/GS in the NICU/PICU/CICU. Abstract : This study shows that a gene panel that includes the majority of known disease‐causing genes can rapidly identify a diagnosis in a large number of tested infants in the NICU/PICU/CICU. This study shows for the first time that rapid sequencing of a panel that includes the majority of known disease‐causing genes has a diagnostic yield similar to previously published rates for rapid exome and genome sequencing. Early diagnosis appeared to have a positive impact on clinical management.